Carboxyl magnetic bead and preparation method thereof

Carboxylic magnetic beads prepared through suspension polymerization and double-layer coating technology solve the problems of uneven particle size and low stability of existing magnetic beads, and improve particle size uniformity and chemical stability. They are suitable for biomedical science and separate fields.

CN119258934AInactive Publication Date: 2025-01-07GUANGZHOU TONGFUGUI CHEM CO LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411226411.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-03
Publication Date
2025-01-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing carboxylic magnetic beads have uneven particle sizes, are prone to agglomeration and have low chemical stability, which affects their application effects in the fields of biomedical and separation.

Method used

Fe3O4/PS/SiO2 microspheres were prepared by suspension polymerization, and polystyrene and silicon layers were coated with double-layers, combined with N (3 aminopropyl) methacrylamide modification to form chain-extended carboxylic magnetic beads to enhance their Dispersibility and stability.

Benefits of technology

It achieves particle size uniformity, reduces agglomeration phenomenon, improves chemical stability and acid-base resistance, and ensures efficient dispersion and stability of magnetic beads.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119258934A_ABST
    Figure CN119258934A_ABST
Patent Text Reader

Abstract

The invention discloses carboxyl magnetic beads and a preparation method thereof, and relates to the technical field of polymer synthesis, a sodium hydroxide solution is prepared and added into a flask, deionized water is used for washing for 2-3 times, vacuum drying is performed for standby application, a suspension polymerization stabilizer and deionized water are added into the flask and stirred and dissolved at room temperature, deionized water and ethyl alcohol are used for washing products in sequence, and the carboxyl magnetic beads are obtained. Performing vacuum drying on the Fe3O4 / PS microspheres for later use, preparing a deionized water / ethanol solution, and adding the deionized water / ethanol solution into a flask; according to the carboxyl magnetic beads and the preparation method thereof, the conversion rate is high, the particle size uniformity degree is high, carboxyl groups are grafted on the surfaces of the microspheres through free radical in-situ polymerization reaction, the carboxyl magnetic beads have the characteristics of high carboxyl grafting rate, uniform distribution and the like, the carboxyl magnetic beads are modified by N (3-aminopropyl) methacrylamide, the steric hindrance among the carboxyl magnetic beads can be increased, and the stability of the magnetic beads is improved. Therefore, dispersity and stability of carboxyl magnetic beads are improved, chemical stability of the carboxyl magnetic beads is guaranteed, and oxidation is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer synthesis, and in particular to carboxyl magnetic beads and a preparation method thereof. Background Art

[0002] Biomagnetic particles are a new type of functional solid carrier. Their surface is modified with active groups and can be coupled with a variety of biologically active substances. They have the characteristics of both liquid fluidity and solid magnetic materials. Carboxyl is an active group commonly used to modify magnetic particles. Under certain conditions, they can be coupled with biological ligands to obtain immunomagnetic beads. Carboxyl-modified magnetic beads use the surface carboxyl groups to react with EDC (1-(3-dimethylaminopropyl)-3-ethylcarbodiimide) / NHS (N-hydroxysuccinimide) to generate NHS-activated magnetic bead intermediates, which are then coupled with the amino groups on the biological ligands using the NHS group. This method has received widespread attention in the fields of biomedicine and separation.

[0003] At present, the conventional structure of carboxyl magnetic beads is a core-shell structure, with the inner layer being magnetic nanoparticles and the outer layer being wrapped with a silicon layer. Carboxyl magnetic beads are obtained by bonding carboxyl groups on the surface through silanol as a functional group. Conventional core-shell carboxyl magnetic beads have some shortcomings: 1. It is impossible to achieve uniformity in particle size, which means that the synthesized magnetic beads can only make a trade-off between uniformity and magnetic responsiveness. The uniformity of particle size will directly affect the effect during extraction. The difference in size will make the extraction effect unstable, and the data obtained from the test will not be accurate. 2. Due to the small size effect and magnetic dipole attraction of the synthesized magnetic core, the magnetic nanoparticles are prone to agglomeration, and the chemical stability is not high and they are easily oxidized.

[0004] Therefore, a carboxyl magnetic bead and a preparation method thereof are proposed to solve the above problems. Summary of the invention

[0005] The main purpose of the present invention is to provide a method for preparing carboxyl magnetic beads with uniform particle size, reduced agglomeration, high stability and low oxidation resistance, which is applied to the preparation of carboxyl magnetic beads by polymer synthesis technology.

[0006] To achieve the above object, the technical solution adopted by the present invention is: a method for preparing carboxyl magnetic beads, the preparation method specifically comprising: Step 1: prepare Fe3O4 magnetic particles, as follows: Prepare sodium hydroxide solution and add it to the flask, stir and heat to 75-85°C, add water to FeCl3·6H2O and FeSO43·7H2O to prepare iron salt solution, and slowly add it to the flask and stir for 0.5-1h, then add ammonia water and continue to react for 1-2h, cool to room temperature after the reaction, perform magnetic separation, wash with deionized water 2-3 times, and vacuum dry for use; Step 2: Preparation of Fe3O4 / PS microspheres, as follows: Add suspension polymerization stabilizer and deionized water into a flask and stir to dissolve at room temperature. Mix Fe3O4 magnetic particles, styrene, crosslinking agent and initiator evenly and add them into the flask. Stir under nitrogen protection. After removing dissolved oxygen in the system, heat to 65-75℃ and react at a constant temperature for 4-5h. Heat to 80-85℃ and react at a constant temperature for 2-3h. After the reaction is completed, cool the product to room temperature, separate the solid and liquid products by magnetic separation, and wash the product with deionized water and ethanol in turn to obtain Fe3O4 / PS microspheres. Vacuum dry and set aside. Step 3: Preparation of Fe3O4 / PS / SiO2 microspheres, as follows: Prepare deionized water / ethanol solution and add it to a flask, add a certain amount of ammonia water and stir to mix evenly, take a certain amount of Fe3O4 / PS microspheres and add them to the flask, stir to fully disperse them evenly, then add ethyl orthosilicate and stir to react at room temperature for 10-12 hours, after the reaction is completed, add silane coupling agent (KH-570) dropwise and stir to react at room temperature for 10-12 hours, after the reaction is completed, perform magnetic separation, and wash with deionized water 2-3 times, disperse the washed product in a certain amount of emulsifier aqueous solution for use; Step 4: Prepare carboxyl-modified Fe3O4 / PS / SiO2 carboxyl magnetic beads, as follows: Take the dispersion in step 3 and add it to a flask, add methacrylic acid (MAA), evacuate the room temperature with nitrogen and stir, heat to 65-75°C, keep warm for 1 hour, add water-soluble initiator and N (3-aminopropyl) methacrylamide, continue to keep warm for 4-5 hours, cool to room temperature after the reaction is completed, perform magnetic separation, wash with deionized water 2-3 times, and vacuum dry to obtain carboxyl magnetic beads.

[0007] The ratio of the sodium hydroxide solution to H2O is 5:100 to 10:100, and the molar ratio of FeCl3·6H2O to FeSO43·7H2Om is 1:0.5 to 1:5.

[0008] The suspension stabilizer is at least one of polyvinyl alcohol (PVA), polymethylpyrrolidone (PVP), sodium polyacrylate and carboxymethyl cellulose.

[0009] The crosslinking agent is at least one of divinylbenzene, allyl methacrylate, trimethylolpropane triacrylate, triallyl isocyanurate, 1,4-butanediol diacrylate, and ethylene glycol dimethacrylate.

[0010] The initiator is at least one of azobisisobutyronitrile, azobisisoheptanenitrile and benzoyl peroxide.

[0011] The mass ratio of water to ethanol is 1:2 to 1:7.

[0012] The mass ratio of the Fe3O4 / PS microspheres to tetraethyl orthosilicate is 1:0.5 to 1:5.

[0013] The mass ratio of the silane coupling agent to tetraethyl orthosilicate is 1:10 to 1:20.

[0014] The emulsifier is at least one of conventional sulfonate emulsifiers, sulfate emulsifiers and sodium lauryl sulfate, preferably sodium lauryl sulfate, and the percentage content in water is 0.05% to 0.15%.

[0015] The mass ratio of the silane coupling agent to methacrylic acid is 1:0.5 to 1:5; The water-soluble initiator is at least one of conventional persulfate and potassium persulfate, preferably potassium persulfate; The mass ratio of the N(3-aminopropyl)methacrylamide to acrylic acid is 1:0.5 to 1:5.

[0016] The present invention has the following beneficial effects: 1. In the present invention, when preparing carboxyl magnetic beads, suspension polymerization is used to prepare micron-sized polystyrene magnetic microspheres, which has the characteristics of simple process, high conversion rate, high uniformity of particle size, and is conducive to subsequent modification. After coating the carboxyl silicon layer, the size can reach 3um, which is much larger than the conventional Fe3O4 / SiO2 core-shell structure magnetic beads. At the same time, they will not agglomerate with each other, and carboxyl groups are grafted on the surface of the microspheres through free radical in-situ polymerization reaction, so they have the characteristics of high carboxyl grafting rate and uniform distribution. 2. In the present invention, Fe3O4 is double-coated with polystyrene and SiO2 layers, and N(3-aminopropyl)methacrylamide is added to modify the carboxyl magnetic beads. The carboxyl magnetic beads are modified into chain-extended carboxyl magnetic beads through the reaction between N(3-aminopropyl)methacrylamide and acrylic acid, which can increase the steric hindrance between the carboxyl magnetic beads, thereby improving the dispersibility and stability of the carboxyl magnetic beads, making the coating of the carboxyl magnetic beads more complete, achieving the characteristics of no magnetic leakage, acid and alkali resistance, etc., ensuring its chemical stability and reducing oxidation. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 The present invention is a schematic diagram of the overall process of carboxyl magnetic beads and a preparation method thereof. DETAILED DESCRIPTION

[0018] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further explained below in conjunction with specific implementation methods.

[0019] Embodiment 1 Please refer to Figure 1 As shown: A carboxyl magnetic bead and a preparation method thereof, comprising the following steps: Step 1: Add 60g NaOH and 600g deionized water to a 2L flask, stir and dissolve, and heat to 75°C. Take 81g FeCl3·6H2O and 41.7g FeSO4·7H2O and add them to 450g water to dissolve to prepare an iron salt solution, and slowly add it to the flask. Keep warm at 75°C for 1h, then add 37.5g concentrated ammonia water and continue to keep warm for 1h. After the reaction is completed, cool to room temperature, perform magnetic separation, wash with deionized water 2-3 times, and vacuum dry to obtain Fe3O4 magnetic particles; Step 2: Add 1g of polyvinyl alcohol and 800g of deionized water to a 2L flask, stir and dissolve, add 20g of Fe3O4 magnetic particles, 180g of styrene, 1.8g of divinylbenzene, and 1g of initiator azobisisobutyronitrile, stir and mix evenly, replace with nitrogen, heat to 70°C and keep warm for 4h, then heat to 80°C and mature for 2h. After the reaction is completed, cool the product to room temperature, separate the solid and liquid products with a magnetic separator, and wash the products with deionized water and ethanol in turn to obtain polystyrene magnetic microspheres, which are then vacuum dried for use; Step 3: Add 800 g of anhydrous ethanol, 200 g of deionized water, and 30 g of ammonia water into a 2L flask and stir to mix evenly. Add 20 g of polystyrene magnetic microspheres and stir and disperse at room temperature for 0.5 h. Add 20 g of tetraethyl orthosilicate and stir to react at room temperature for 12 h. Add 1.5 g of silane coupling agent (KH-570) and stir to react at room temperature for 12 h. Use a magnetic separator to separate the solid and liquid products and wash the product with deionized water for 2-3 times to obtain Fe3O4 / PS / SiO2 microspheres.

[0020] Step 4: Add the obtained Fe3O4 / PS / SiO2 microspheres into a 2L flask, add 700g water and 0.8g sodium dodecyl sulfate, stir and disperse evenly, add 2.5g methacrylic acid, replace with nitrogen, stir and heat to 75℃ for 1h, then add 1.5g potassium persulfate to initiate polymerization for 5h. After the reaction is complete, add water-soluble initiator and N(3-aminopropyl)methacrylamide, cool to room temperature, separate the solid and liquid products with a magnetic separator and wash the products with deionized water for 2-3 times to obtain carboxyl magnetic beads. The ratio of sodium hydroxide solution to H2O is 5:100 to 10:100, and the molar ratio of FeCl3·6H2O to FeSO43·7H2Om is 1:0.5 to 1:5.

[0021] The suspension stabilizer is at least one of polyvinyl alcohol (PVA), polymethylpyrrolidone (PVP), sodium polyacrylate and carboxymethyl cellulose.

[0022] The crosslinking agent is at least one of divinylbenzene, allyl methacrylate, trimethylolpropane triacrylate, triallyl isocyanurate, 1,4-butanediol diacrylate, and ethylene glycol dimethacrylate.

[0023] Micron-sized polystyrene magnetic microspheres are prepared by suspension polymerization, which has the characteristics of simple process, high conversion rate, high uniformity of particle size, and is conducive to subsequent modification. After being coated with a carboxyl silicon layer, the size can reach 3um, which is much larger than conventional Fe3O4 / SiO2 core-shell structure magnetic beads.

[0024] Embodiment 2 The same as Example 1, only the amount of polyvinyl alcohol in step 2 is adjusted to 2 g, a carboxyl magnetic bead and a preparation method thereof specifically include the following steps: Step 1: Add 60g NaOH and 600g deionized water to a 2L flask, stir and dissolve, and heat to 75°C. Take 81g FeCl3·6H2O and 41.7g FeSO4·7H2O and add them to 450g water to dissolve to prepare an iron salt solution, and slowly add it to the flask. Keep warm at 75°C for 1h, then add 37.5g concentrated ammonia water and continue to keep warm for 1h. After the reaction is completed, cool to room temperature, perform magnetic separation, wash with deionized water 2-3 times, and vacuum dry to obtain Fe3O4 magnetic particles; Step 2: Add 2g of polyvinyl alcohol and 800g of deionized water to a 2L flask and stir to dissolve. Add 20g of Fe3O4 magnetic particles, 180g of styrene, 1.8g of divinylbenzene, and 1g of initiator azobisisobutyronitrile and stir to mix evenly. After nitrogen replacement, heat to 70℃ and keep warm for 4h, then heat to 80℃ and mature for 2h. After the reaction is completed, cool the product to room temperature, separate the solid and liquid products with a magnetic separator, and wash the products with deionized water and ethanol in turn to obtain polystyrene magnetic microspheres, which are then vacuum dried for use. Step 3: Add 800 g of anhydrous ethanol, 200 g of deionized water, and 30 g of ammonia water into a 2L flask and stir to mix evenly. Add 20 g of polystyrene magnetic microspheres and stir and disperse at room temperature for 0.5 h. Add 20 g of tetraethyl orthosilicate and stir to react at room temperature for 12 h. Add 1.5 g of silane coupling agent (KH-570) and stir to react at room temperature for 12 h. Use a magnetic separator to separate the solid and liquid products and wash the product with deionized water for 2-3 times to obtain Fe3O4 / PS / SiO2 microspheres.

[0025] Step 4: Add the obtained Fe3O4 / PS / SiO2 microspheres into a 2L flask, add 700g water and 0.8g sodium dodecyl sulfate and stir to disperse evenly, add 2.5g methacrylic acid, replace with nitrogen, stir and heat to 75℃ for 1h, then add 1.5g potassium persulfate to initiate polymerization for 5h. After the reaction is complete, add water-soluble initiator and N(3-aminopropyl)methacrylamide, cool to room temperature, separate the solid and liquid products with a magnetic separator and wash the product with deionized water 2-3 times to obtain carboxyl magnetic beads.

[0026] The initiator is at least one of azobisisobutyronitrile, azobisisoheptanenitrile and benzoyl peroxide.

[0027] The mass ratio of water to ethanol is 1:2 to 1:7.

[0028] The mass ratio of Fe3O4 / PS microspheres to tetraethyl orthosilicate is 1:0.5 to 1:5.

[0029] The mass ratio of the silane coupling agent to the tetraethyl orthosilicate is 1:10 to 1:20.

[0030] By adding polyvinyl pyrrolidone (PVP), first of all, polyvinyl pyrrolidone (PVP) is a stabilizer commonly used in dispersion polymerization. In the dispersion polymerization of preparing polystyrene microspheres, PVP can be used as a stabilizer. Through its stereostabilizing effect, the microspheres can be stably present in the emulsion, reducing agglomeration, and combining polyvinyl pyrrolidone with N (3-aminopropyl) methacrylamide. The amino group of N (3-aminopropyl) methacrylamide can react with the carboxyl group to form an amide bond, and its double bond can participate in free radical polymerization, thereby forming a stable polymer layer on the surface of the magnetic beads. This not only increases the stability of the carboxyl magnetic beads, but also adjusts the surface properties of the magnetic beads by changing the composition of the polymer layer, so that the carboxyl magnetic beads further reduce agglomeration, and grafts carboxyl groups on the surface of the microspheres through free radical in situ polymerization, which has the characteristics of high carboxyl grafting rate and uniform distribution.

[0031] Embodiment 3 The same as Example 1, only the amount of polyvinyl alcohol in step 2 is adjusted to 4 g, a carboxyl magnetic bead and a preparation method thereof specifically include the following steps: Step 1: Add 60g NaOH and 600g deionized water to a 2L flask, stir and dissolve, and heat to 75°C. Take 81g FeCl3·6H2O and 41.7g FeSO4·7H2O and add them to 450g water to dissolve to prepare an iron salt solution, and slowly add it to the flask. Keep warm at 75°C for 1h, then add 37.5g concentrated ammonia water and continue to keep warm for 1h. After the reaction is completed, cool to room temperature, perform magnetic separation, wash with deionized water 2-3 times, and vacuum dry to obtain Fe3O4 magnetic particles; Step 2: Add 4g of polyvinyl alcohol and 800g of deionized water to a 2L flask and stir to dissolve. Add 20g of Fe3O4 magnetic particles, 180g of styrene, 1.8g of divinylbenzene, and 1g of initiator azobisisobutyronitrile and stir to mix evenly. After nitrogen replacement, heat to 70℃ and keep warm for 4h, then heat to 80℃ and mature for 2h. After the reaction is completed, cool the product to room temperature, separate the solid and liquid products with a magnetic separator, and wash the products with deionized water and ethanol in turn to obtain polystyrene magnetic microspheres, which are then vacuum dried for use. Step 3: Add 800 g of anhydrous ethanol, 200 g of deionized water, and 30 g of ammonia water into a 2L flask and stir to mix evenly. Add 20 g of polystyrene magnetic microspheres and stir and disperse at room temperature for 0.5 h. Add 20 g of tetraethyl orthosilicate and stir to react at room temperature for 12 h. Add 1.5 g of silane coupling agent (KH-570) and stir to react at room temperature for 12 h. Use a magnetic separator to separate the solid and liquid products and wash the product with deionized water for 2-3 times to obtain Fe3O4 / PS / SiO2 microspheres.

[0032] Step 4: Add the obtained Fe3O4 / PS / SiO2 microspheres into a 2L flask, add 700g water and 0.8g sodium dodecyl sulfate and stir to disperse evenly, add 2.5g methacrylic acid, replace with nitrogen, stir and heat to 75℃ for 1h, then add 1.5g potassium persulfate to initiate polymerization for 5h. After the reaction is complete, add water-soluble initiator and N(3-aminopropyl)methacrylamide, cool to room temperature, separate the solid and liquid products with a magnetic separator and wash the product with deionized water 2-3 times to obtain carboxyl magnetic beads.

[0033] The emulsifier is at least one of conventional sulfonate emulsifiers, sulfate emulsifiers and sodium lauryl sulfate, preferably sodium lauryl sulfate, and the percentage content in water is 0.05% to 0.15%.

[0034] The mass ratio of the silane coupling agent to methacrylic acid is 1:0.5 to 1:5; The water-soluble initiator is at least one of conventional persulfate and potassium persulfate, preferably potassium persulfate; The mass ratio of N(3-aminopropyl)methacrylamide to acrylic acid is 1:0.5 to 1:5.

[0035] After Fe3O4 is double-coated with polystyrene and SiO2 layers, N (3-aminopropyl) methacrylamide is added at the same time. The carboxyl magnetic beads can be modified with N (3-aminopropyl) methacrylamide to modify the carboxyl magnetic beads into chain-extended carboxyl magnetic beads, thereby increasing the steric hindrance between the carboxyl magnetic beads, improving the dispersibility and stability of the carboxyl magnetic beads, making the coating of the carboxyl magnetic beads more complete, achieving the characteristics of no magnetic leakage, acid and alkali resistance, ensuring its chemical stability and reducing oxidation.

[0036] The particle size of the magnetic beads obtained in Examples 1 to 3 was tested using a dynamic optical diffraction analyzer. During the test, a small drop of the sample to be tested was added to the sample tank. After multiple dilutions, the conductivity of the sample was between 100 and 800 kcps. Each sample was tested 5 times in parallel and the average value was taken. The test results are shown in Table 1:

[0037] From the test results in Table 1 above, it can be seen that for the carboxyl magnetic beads prepared in Examples 1 to 3, the more the amount of dispersion stabilizer used, the smaller the particle size, and the lower the corresponding particle size dispersion coefficient, indicating that the particle size distribution is more concentrated and the uniformity is better. It can be seen from the test results that the prepared carboxyl magnetic beads have uniform particle size, reduced agglomeration, high stability and are not easy to oxidize.

[0038] The present invention provides a carboxyl magnetic bead and a preparation method thereof. In the operation of the method, a sodium hydroxide solution is first prepared and added to a flask, stirred and heated to 75-85°C, FeCl3·6H2O and FeSO43·7H2O are added with water to prepare an iron salt solution, and the solution is slowly added to the flask and stirred for 0.5-1h, and then ammonia water is added to continue the reaction for 1-2h. After the reaction is completed, the solution is cooled to room temperature, magnetic separation is performed, and the solution is washed with deionized water for 2-3 times, and then vacuum dried for standby use; a suspension polymerization stabilizer and deionized water are added to the flask, stirred and dissolved at room temperature, and Fe3O4 The magnetic particles, styrene, crosslinking agent and initiator are mixed evenly and added to the flask, and stirred under nitrogen protection. After the dissolved oxygen in the system is eliminated, the mixture is heated to 65-75°C for constant temperature reaction for 4-5 hours, and then heated to 80-85°C for constant temperature reaction for 2-3 hours. After the reaction is completed, the product is cooled to room temperature, the solid and liquid products are separated by magnetic separation, and the products are washed with deionized water and ethanol in sequence to obtain Fe3O4 / PS microspheres, which are then dried in vacuo for later use. A deionized water / ethanol solution is prepared and added to the flask, and a certain amount of ammonia water is added and stirred to mix evenly. A certain amount of Fe3O4 / P S microspheres are added to the flask and stirred to disperse evenly. Then, ethyl orthosilicate is added and stirred at room temperature for 10-12 hours. After the reaction is completed, silane coupling agent (KH-570) is added dropwise and stirred at room temperature for 10-12 hours. After the reaction is completed, magnetic separation is performed and washed with deionized water for 2-3 times. The washed product is dispersed in a quantitative emulsifier aqueous solution for standby use. The micron-sized polystyrene magnetic microspheres are prepared by suspension polymerization, which has the characteristics of simple process, high conversion rate, high uniformity of particle size, and is conducive to subsequent modification. After coating with carboxyl silicon layer, its size can reach 3um, which is much larger than that of ordinary The Fe3O4 / SiO2 core-shell structure of the magnetic beads is regular and will not agglomerate with each other. Carboxyl groups are grafted on the surface of the microspheres through free radical in-situ polymerization reaction, and have the characteristics of high carboxyl grafting rate and uniform distribution. The dispersion in step 3 is added to a flask, and methyl acrylic acid (MAA) is added. After vacuuming and replacing with nitrogen at room temperature, the temperature is raised to 65-75°C and kept warm for 1 hour. After the insulation is completed, a water-soluble initiator and N (3-aminopropyl) methacrylamide are added, and the insulation is continued for 4-5 hours. After the reaction is completed, the temperature is lowered to room temperature, and magnetic separation is performed. The MAA is washed with deionized water for 2-3 times and vacuumed. After drying, carboxyl magnetic beads can be obtained. Fe3O4 is double-coated with polystyrene and SiO2 layers. At the same time, by adding N (3-aminopropyl) methacrylamide, the carboxyl magnetic beads can be modified with N (3-aminopropyl) methacrylamide. Through the reaction between N (3-aminopropyl) methacrylamide and acrylic acid, the carboxyl magnetic beads are modified into chain-extended carboxyl magnetic beads, which can increase the steric hindrance between the carboxyl magnetic beads, thereby improving the dispersibility and stability of the carboxyl magnetic beads, making the coating of the carboxyl magnetic beads more complete, achieving the characteristics of no magnetic leakage, acid and alkali resistance, etc., ensuring its chemical stability and reducing oxidation.

[0039] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A method for preparing carboxyl magnetic beads, characterized in that, The preparation method is specifically: Step 1: prepare Fe3O4 magnetic particles, as follows: Prepare sodium hydroxide solution and add it to the flask, stir and heat to 75-85°C, add water to FeCl3·6H2O and FeSO43·7H2O to prepare iron salt solution, and slowly add it to the flask and stir for 0.5-1h, then add ammonia water and continue to react for 1-2h, cool to room temperature after the reaction, perform magnetic separation, wash with deionized water 2-3 times, and vacuum dry for use; Step 2: Preparation of Fe3O4 / PS microspheres, as follows: Add suspension polymerization stabilizer and deionized water into a flask and stir to dissolve at room temperature. Mix Fe3O4 magnetic particles, styrene, crosslinking agent and initiator evenly and add them into the flask. Stir under nitrogen protection. After removing dissolved oxygen in the system, heat to 65-75℃ and react at a constant temperature for 4-5h. Heat to 80-85℃ and react at a constant temperature for 2-3h. After the reaction is completed, cool the product to room temperature, separate the solid and liquid products by magnetic separation, and wash the product with deionized water and ethanol in turn to obtain Fe3O4 / PS microspheres. Vacuum dry and set aside. Step 3: Preparation of Fe3O4 / PS / SiO2 microspheres, as follows: Prepare deionized water / ethanol solution and add it to a flask, add a certain amount of ammonia water and stir to mix evenly, take a certain amount of Fe3O4 / PS microspheres and add them to the flask, stir to fully disperse them evenly, then add ethyl orthosilicate and stir to react at room temperature for 10-12 hours, after the reaction is completed, add silane coupling agent (KH-570) dropwise and stir to react at room temperature for 10-12 hours, after the reaction is completed, perform magnetic separation, and wash with deionized water 2-3 times, disperse the washed product in a certain amount of emulsifier aqueous solution for use; Step 4: Prepare carboxyl-modified Fe3O4 / PS / SiO2 carboxyl magnetic beads, as follows: Take the dispersion in step 3 and add it to a flask, add methacrylic acid (MAA), evacuate the room temperature with nitrogen and stir, heat to 65-75°C, keep warm for 1 hour, add water-soluble initiator and N (3-aminopropyl) methacrylamide, continue to keep warm for 4-5 hours, cool to room temperature after the reaction is completed, perform magnetic separation, wash with deionized water 2-3 times, and vacuum dry to obtain carboxyl magnetic beads.

2. The preparation method according to claim 1, characterized in that: The ratio of the sodium hydroxide solution to H2O is 5:100 to 10:100, and the molar ratio of FeCl3·6H2O to FeSO43·7H2Om is 1:0.5 to 1:

5.

3. The preparation method according to claim 1, characterized in that: The suspension stabilizer is at least one of polyvinyl alcohol (PVA), polymethylpyrrolidone (PVP), sodium polyacrylate and carboxymethyl cellulose.

4. The preparation method according to claim 1, characterized in that: The crosslinking agent is at least one of divinylbenzene, allyl methacrylate, trimethylolpropane triacrylate, triallyl isocyanurate, 1,4-butanediol diacrylate, and ethylene glycol dimethacrylate.

5. The preparation method according to claim 1, characterized in that: The initiator is at least one of azobisisobutyronitrile, azobisisoheptanenitrile and benzoyl peroxide.

6. The preparation method according to claim 1, characterized in that: The mass ratio of water to ethanol is 1:2 to 1:

7.

7. The preparation method according to claim 1, characterized in that: The mass ratio of the Fe3O4 / PS microspheres to tetraethyl orthosilicate is 1:0.5 to 1:

5.

8. The preparation method according to claim 1, characterized in that: The mass ratio of the silane coupling agent to tetraethyl orthosilicate is 1:10 to 1:

20.

9. The preparation method according to claim 1, characterized in that: The emulsifier is at least one of conventional sulfonate emulsifiers, sulfate emulsifiers and sodium lauryl sulfate, preferably sodium lauryl sulfate, and the percentage content in water is 0.05% to 0.15%.

10. The preparation method according to claim 1, characterized in that: The mass ratio of the silane coupling agent to methacrylic acid is 1:0.5 to 1:5; The water-soluble initiator is at least one of conventional persulfate and potassium persulfate, preferably potassium persulfate; The mass ratio of the N(3-aminopropyl)methacrylamide to acrylic acid is 1:0.5 to 1:5.

Citation Information

Patent Citations

  • Super-hydrophobic and magnetic PS / SiO2 oil-water separation material and preparation method thereof

    CN106277162A

  • Preparation method of CD133 immunomagnetic beads

    CN107389916A

  • Monodisperse superparamagnetic carboxyl silicon magnetic beads and preparation method thereof

    CN111995720A

  • Polymer coated magnetic microsphere and preparation method thereof

    CN114093586A